(untitled) (Lapai Journal of Economics, 2023)
Interconnected economies in the world commodity market may cause external shocks that slow indigenous countries’ economic growth and development. Nigeria is a commodity-dependent country, hence, commodity price shocks have harmed its institutional and fiscal framework for economic growth, despite efforts to save the economy. It is crucial to assess the effects of local and external commodity price volatility shocks on emerging nations’ growth since they plunge millions into abject poverty. It is in this context, this study examines commodity price shock and economic performance with an empirical evidence for Nigeria. This study employs Multivariate Generalized Autoregressive Conditional Heteroscedasticity (MGARCH) to capture both gradual and unexpected changes in commodity price shock in Nigeria from 1980Q1 – 2021Q1. The results showed positive volatility shock effect on each variable caused by its past innovations while parameters of the independent variables indicated innovations of shock effects on economic performance. Also exports of other non-oil commodities can reduce dependence of real exchange rate on world commodity prices by having more diversified exports. The study recommends for diversification towards agricultural production to stabilize the real exchange rate of Naira from world commodity price shocks. Finally, Nigeria can protect her competitiveness from fluctuations in world commodity prices by being more opened to external trade.